Impact of 18F-fluorodeoxyglucose positron emission tomography/computed tomography staging in newly diagnosed classical Hodgkin lymphoma: fewer cases with stage I disease and more with skeletal involvement. Issue 10 (October 2014) - El-Galaly, Tarec Christoffer; Hutchings, Martin; Mylam, Karen Juul; Brown, Peter de Nully; Bukh, Anne; Johnsen, Hans Erik; Kamper, Peter; Loft, Annika; Iyer, Victor; Gormsen, Lars Christian; Nielsen, Anne Lerberg; Bøgsted, Martin; et al.
Abstract 18F-Fluorodeoxyglucose positron emission tomography/ computed tomography (PET/CT) is a highly accurate staging method in classical Hodgkin lymphoma (cHL). We retrospectively compared the staging results obtained in two large cohorts of patients with cHL diagnosed before (n = 324) and after (n = 406) the introduction of PET/CT staging in a retrospective study. In PET/CT staged patients, stage I disease was less frequent (16% vs. 27%, p < 0.001) while stage IV disease was more frequent (17% vs. 10%, p = 0.02). Imaging-detected skeletal involvement was recognized more often in PET/CT staged patients (17% vs. 2%, p < 0.001), and the presence of focal skeletal PET/CT lesions was associated with higher risk of progression (hazard ratio [HR] 1.96, 95% confidence interval [CI]: 1.14–3.36). The German Hodgkin Study Group (GHSG) risk classification (early, intermediate, advanced disease) predicted outcome in PET/CT staged patients. In conclusion, PET/CT led to higher disease stages, and the more frequently diagnosed skeletal lesions may be an adverse prognostic factor.